THE IMPORTANCE OF INNOVATIVE MARKETING TECHNOLOGIES IN THE DIGITAL ECONOMY (World Economics and Finance Bulletin, 2023)
The article is based on the use of innovative marketing technologies in the development of the service sector and its importance today. Also, specific aspects of marketing technologies, theoretical and practical issues are included
Keywords: innovative marketing; innovative marketing technologies; digital marketing